Measuring the Interaction Between the Macro- and Micro-Vasculature - Climie, Rachel E.; Gallo, Antonio; Picone, Dean S.; Di Lascio, Nicole; van Sloten, Thomas T.; Guala, Andrea; Mayer, Christopher C.; Hametner, Bernhard; Bruno, Rosa Maria (Frontiers in Cardiovascular Medicine, 2019)
Structural and functional dysfunction in both the macro- and microvasculature are a feature of essential hypertension. In a healthy cardiovascular system, the elastic properties of the large arteries ensure that pulsations in pressure and flow generated by cyclic left ventricular contraction are dampened, so that less pulsatile pressure and flow are delivered at the microvascular level. However, in response to ageing, hypertension and other disease states, arterial stiffening limits the buffering capacity of the elastic arteries, thus exposing the microvasculature to increased pulsatile stress. This is thought to be particularly pertinent to high flow / low resistance organs such as the brain and kidney, which may be sensitive to excess pressure and flow pulsatility, damaging capillary networks and resulting in target organ damage. In this review, we describe the clinical relevance of the pulsatile interaction between the macro- and microvasculature and summarize current methods for measuring the transmission of pulsatility between the two sites.